Adaptive active suspension levelling control system based on ARM embedded system - Zhang, Pengchao; Zhang, Pan; Yue, Huijun; Gu, Jie; Yu, Hongjun; Wang, Yongchang (SPIE, 2024)
The control system of the adaptive active suspension system was built, which used the hydraulic system as the balancing method, and used STM32, remote control, gyroscope, oil pump motor, solenoid valve, relay module, high-precision current analog output module and other modules. Kalman filter, PID and other algorithms are used to realize the automatic leveling of the adaptive active suspension. The automatic leveling of the adaptive active suspension is tested, and it is shown that after setting the angle deviation threshold, the control system and the applied algorithm can quickly and accurately adjust the deviation angle of the whole vehicle within the threshold. The leveling control system can be widely used in emergency rescue, agricultural picking and other fields, and has strong practical significance.